Adverse dermatoneurological events and impacts on daily activities of patients with gastrointestinal neoplasms undergoing chemotherapy - Rafaela Moreira da Silva Canille; Maria Helena Pinto; Katia Jaira Galisteu; Rildo César Czorny; Luana Gaino Bertolazzi; Tamara Veiga Faria (Revista Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to associate the presence and grading of adverse dermatoneurological events (peripheral neuropathy and hand-foot syndrome) and the interference in the activities of daily living of patients with gastrointestinal neoplasms undergoing systemic antineoplastic treatment. Method: this is a longitudinal, prospective study, using instruments to assess hand-foot syndrome and peripheral neuropathy. Results: there were 36 patients: 66.7% diagnosed with colon cancer and 83.2% on combination therapy. From cycle 5 onwards, all of them had hand-foot syndrome, with a majority of grade 1, unrelated to interference in activities of daily living. Regarding peripheral neuropathy, there was a moderate to strong correlation from cycle 1 of treatment. Conclusion: peripheral neuropathy negatively affects activities of daily living. The monitoring of dermatoneurological events by oncology nurses contributes to the clinical practice of nursing and subsidizes the development of advanced practice in the country.